Comparative Experiences of EFL Students Using Gamified Versus Traditional Web-Based Grammar Practice: A Qualitative Case Study - Baidawi, Achmad; Rabi’ah, Rabi’ah; Habibullah, Mosleh; Virdyna, Nina Khayatul (PANYONARA: Journal of English Education, 2025)
The increasing use of digital tools in English as a Foreign Language (EFL) instruction has transformed grammar learning, offering contrasting affordances. This study explored how university-level EFL students in Indonesia experience gamified (Quizizz) versus traditional web-based grammar platforms. Adopting a qualitative case study with 30 participants, data were collected through classroom observations and semi-structured questionnaires based on 15 behaviorally anchored indicators aligned with three research questions. Findings revealed that Quizizz heightened engagement through competitive elements, immediate feedback, and peer interactionâ€”though some learners experienced stress due to time constraints. In contrast, traditional grammar websites promoted self-paced study, detailed explanations, and conceptual clarity, albeit with lower interaction and occasional disengagement. Cross-platform comparison showed learners valued both tools: Quizizz for motivational drill practice and traditional platforms for in-depth understanding and exam preparation. These insights suggest that neither platform alone is universally optimal. A blended instructional approach, combining gamified engagement with structured guidance, offers a more balanced grammar learning experience tailored to diverse learner preferences. Future research should include longitudinal and comparative designs across proficiency levels and integrate theoretical perspectives such as Self-Determination Theory and the Technology Acceptance Model to further elucidate learners’ motivation and platform use.